2020
DOI: 10.1155/2020/8104538
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis, Cytotoxic, Antioxidant, and Antibacterial Activities of Lichens

Abstract: Background. Lichens present a complex symbiotic relationship between a filamentous fungus, photoautotrophic partner (algae or cyanobacteria), and bacterial community. The Objective of the Study. This study aimed at investigating the chemical composition and cytotoxic, antioxidant, and antimicrobial activities of acetone extracts of Moroccan Evernia prunastri (E. prunastri), Ramalina farinacea (R. farinacea), and Pseudevernia furfuracea (P. furfuracea). Materials and Methods. The phytochemical analysis was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 39 publications
(34 reference statements)
1
17
0
Order By: Relevance
“…Extracts from E. prunastri , in the turn, showed moderate antioxidant activity comparing to usnic acid and a lower number of phenols. Obtained results are corresponding to the published ones (Mitrović et al 2011 ; Hawrył et al 2020 ; Aoussar et al 2020 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Extracts from E. prunastri , in the turn, showed moderate antioxidant activity comparing to usnic acid and a lower number of phenols. Obtained results are corresponding to the published ones (Mitrović et al 2011 ; Hawrył et al 2020 ; Aoussar et al 2020 ).…”
Section: Discussionsupporting
confidence: 87%
“…There is less information about the antimicrobial activity of E. prunastri. An acetone extract from E. prunastri has been published to be active against S. aureus at the concentration range of 0.078-0.5 mg/ml and a MRSA clinical isolate at the concentration of 0.039 mg/ml (Tapalsky et al 2017;Aoussar et al 2020). A methanol extract was active at the concentration of 0.156 mg/ml (Mitrović et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, methanolic and ethyl acetate extracts from the lichen Umbilicaria cylindrica demonstrated important antimicrobial activity against eight strains, including S. aureus , E. coli and C. albicans , with MIC values ranging from 15.62 to 62.50 μg/mL [ 34 ]. Other reports indicated that extracts from the two lichens Evernia prunastri and Pseudevernia furfuracea exhibited a higher antibacterial effect vs. five clinical isolates of methicillin-resistant S. aureus , with MIC values of 0.039 to 0.15 mg/mL, and extracts of Ramalina farinacea possessed MIC values in the range of 0.078–0.625 mg/mL [ 35 ]. The antimicrobial effect of LPVC could be explained by the presence of a high level of the sesquiterpene himachalene derivatives, since a positive correlation between these compounds and the antimicrobial activity was proved [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, two microbial colonies were collected from a fresh culture after 24 h in Mueller–Hinton agar (MHA) and Sabouraud Agar (SBA) media and then suspended in 0.9% NaCl solution. Subsequently, the suspension turbidity was adjusted to be 0.5 McFarland [ 78 ]. For the mold species, the inoculum was prepared by the conidial suspension.…”
Section: Methodsmentioning
confidence: 99%